The Impact of Students' Learning Motivation On Learning-Based E-Learning IPS & PKN - Vani Qhairum Nisa Utami; Yeni Erita; Feby KURNIAWAN; Didi SYAHRIL (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
A Study to Encourage Online Learning and Student Learning for IPS and PKN Online Learning. The method is literature and qualitative research. A study that analyzes some magazines or articles from previous studies related to the research topic. Data collection was done using web tracking, searching journals or articles using Google Scholar. The results of the analysis of several journals revealed that the learning motivation of students of social sciences and work practice plays an important role in the success of learning. By accessing online learning, students can easily learn the features that already exist in both distance learning and online learning so that learning can also be applied in elementary schools.